Pengaruh Disiplin Kerja terhadap Kinerja Karyawan melalui Komitmen Karyawan pada PT Gunung Mutiara Nedindo - Sandi Nur Fikri; Zahara Tussoleha Rony; Djundi Thamrin (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2026)
This study aims to analyze how work discipline affects employee performance through employee commitment at PT Gunung Mutiara Nedindo. This study uses a quantitative approach with a survey method. Data were obtained by distributing questionnaires to employees of PT Gunung Mutiara Nedindo. The variables in this study include work discipline as the independent variable, employee commitment as the mediating variable, and employee performance as the dependent variable. The data analysis technique used path analysis to examine both direct and indirect effects among variables. The results indicate that work discipline has a positive and significant effect on employee performance. Work discipline also has a positive and significant effect on employee commitment, and employee commitment has a positive and significant effect on employee performance. Furthermore, employee commitment is proven to mediate the relationship between work discipline and employee performance. These findings suggest that improving work discipline accompanied by strengthening employee commitment can enhance employee performance more effectively and sustainably. Therefore, organizations are encouraged to implement consistent disciplinary policies and develop strategies to strengthen employee commitment in order to achieve optimal organizational performance